2001
DOI: 10.1175/1520-0485(2001)031<3374:ogccaw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Gyre Circulation Changes Associated with the North Atlantic Oscillation*

Abstract: Observational evidence is presented for interannual to interdecadal variability in the intensity of the North Atlantic gyre circulation related to the atmospheric North Atlantic Oscillation (NAO) patterns. A two-point baroclinic pressure difference between the subtropical and subpolar gyre centers-an oceanic analogue to the much-used sea level pressure (SLP)-based atmospheric NAO indices-is constructed from time series of potential energy anomaly (PEA) derived from hydrographic measurements in the Labrador Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
263
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(312 citation statements)
references
References 87 publications
40
263
2
5
Order By: Relevance
“…Its time evolution (BTSF PC1) is discussed in Hátún et al (2005a), MHS, and DF08. It tends to lag the NAO by 2 years, and is broadly consistent with the transport indices of Curry and McCartney (2001) and the altimetry data of Häkkinen and Rhines (2004). BTSF PC1 is well correlated with MOC PC1 (all correlations are given for linearly detrended data, even though the trend is not removed when displaying the time series), such that the strengthening of the Atlantic MOC after a positive NAO phase is accompanied by an intensification of the subpolar and subtropical gyres (Fig.…”
Section: Circulation Variabilitysupporting
confidence: 77%
“…Its time evolution (BTSF PC1) is discussed in Hátún et al (2005a), MHS, and DF08. It tends to lag the NAO by 2 years, and is broadly consistent with the transport indices of Curry and McCartney (2001) and the altimetry data of Häkkinen and Rhines (2004). BTSF PC1 is well correlated with MOC PC1 (all correlations are given for linearly detrended data, even though the trend is not removed when displaying the time series), such that the strengthening of the Atlantic MOC after a positive NAO phase is accompanied by an intensification of the subpolar and subtropical gyres (Fig.…”
Section: Circulation Variabilitysupporting
confidence: 77%
“…Ezer (2013) and Ezer et al (2013) suggested that the weakening Gulf Stream and AMOC, which affect the hotspot SLR acceleration during recent decades, are linked to the Atlantic Multidecadal Oscillation (AMO) but are also affected by the SLP and winds associated with the NAO. The effects of NAO-related wind stress curl and surface heat flux in the basin interior on interannual and decadal variability of the Gulf Stream have also been suggested by other studies (e.g., Curry and McCartney 2001;Di Nezio et al 2009;Chaudhuri et al 2011). This effect is shown to be important from 1986 to 1998 compared to the periods before and after (Meinen et al 2010).…”
Section: Nao-related Sea Level Patternssupporting
confidence: 70%
“…1), at a lag of almost one year. This lag is similar to the response time of the Subtropical Gyre and Gulf Stream circulations to NAO forcing (e.g., Curry and McCartney, 2001), which hints at potential changes in the local water mass composition driving the Sr/Ca signal. The coral record shows a subdecadal variability (7.5-year cycle) that compares well with that of the NAO index, while the long-term trend (e.g.…”
Section: Coral Recordssupporting
confidence: 57%